2018
DOI: 10.1016/j.jhydrol.2018.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of sea-level rise on steady-state seawater intrusion in a layered coastal aquifer

Abstract: Previous studies on the impact of sea-level rise (SLR) on seawater intrusion (SWI) are mostly based on the assumption of a homogeneous coastal aquifer. In this study, we extend those studies by investigating SLR-induced SWI in a layered coastal aquifer using the analytical method developed by Strack and Ausk (2015). We provide analytical solutions for steady-state SWI in confined and unconfined coastal aquifers, where both constant-head and constant-flux inland boundary conditions are considered. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
4
15
1
Order By: Relevance
“…A coastal stratum deposit is affected by the alluvial-diluvial effects of coastal rivers and presents the stratification phenomenon. Some scholars have studied the law of seawater intrusion in the multi-layered aquifer system [7,19,21,42,[53][54][55][56][57]. A few studies have considered seawater intrusion under the influence of pumping in multi-layered aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…A coastal stratum deposit is affected by the alluvial-diluvial effects of coastal rivers and presents the stratification phenomenon. Some scholars have studied the law of seawater intrusion in the multi-layered aquifer system [7,19,21,42,[53][54][55][56][57]. A few studies have considered seawater intrusion under the influence of pumping in multi-layered aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of flow models were developed for seawater intrusion simulation, including the sharp interface models and mixing interface models [14,[19][20][21][22][23][24]. There are many analytical solutions for variable density flow models to solve the coupled seawater intrusion equations under special conditions [6,19,20,25]. Most of the analytical solutions are predominantly based on the Ghyben-Herzberg relation in the sharp interface models, in which the freshwater and saltwater are treated as separated fluids by an interface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have concentrated on different types of heterogeneity and their proper solutions [10,[20][21][22][23]. Shi et al [24] examined the effect of layered coastal aquifer on SWI by using the analytical method developed by Strack and Ausk (2015) [21]. Their results indicated that in general the initial location and response distance of the interface toe were affected by aquifer stratification [24].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [24] examined the effect of layered coastal aquifer on SWI by using the analytical method developed by Strack and Ausk (2015) [21]. Their results indicated that in general the initial location and response distance of the interface toe were affected by aquifer stratification [24]. For stratified aquifers, Lu et al [25] conducted a series of experiments and numerical simulations to investigate the effect of parameters involved in SWI.…”
Section: Introductionmentioning
confidence: 99%